The Meaning of the Phrase “Temporary Absent” Performing His Position as a Notary - I Nyoman Sujana; I Made Pria Dharsana; Ni Putu Indianita Cahyanti (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2022)
This paper analyses the meaning of the phrase of being temporary unable to carry out his position as a Notary. The focus of the study in this paper is regarding the phrase unable to carry out his position as a notary as referred to in Article 1 point 3 UUJN jo. UUJN-P. The method used is a normative legal writing method, using a statutory approach, a case approach, and a conceptual approach that is also supported by a factual approach. As an analytical tool for the legal issues studied, the author uses the theory of legal certainty and the theory of hermeneutics. These two theories are used because this paper aims to analyse clearly the meaning of the phrase unable to carry out his position as a notary, so that it does not cause multiple interpretations. The legal materials used are primary legal materials in the form of legislation related to the Notary Position, which is complemented by secondary legal materials in the form of reputable journals and the latest literature. Based on the results of the analysis, it can be found that the meaning of the phrase temporary absent can be interpreted as a form of leave granted by UUJN and UUJN-P with a maximum of 12 years, except for a notary who is appointed as a state official. Serving as a state official, and should not be interpreted as a temporary dismissal. The purpose of this analysis is to provide legal certainty over the meaning of the phrase unable to carry out his position as a notary.